BLENDED LEARNING SEBAGAI SARANA OPTIMALISASI PEMBELAJARAN DARING DI ERA NEW NORMAL - Medina Nur Asyifah Purnama (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2020)
Abstract; Writing this article aims to analyze in a literature review the importance of combined learning or blended learning using synchronous and asynchronous strategies as a means of optimizing the learning process in the current Covid 19 pandemic era. In this article, there are four steps taken to analyze the data, namely determining the theme to be reviewed, selecting and selecting articles according to the theme, reviewing and synthesizing literature and compiling it into a writing. The results of the literature review show that the optimization of the learning process in the current Covid 19 and New Normal pandemic era will be effective and efficient by using the blended learning method where the learning process combines the two existing strategies in blended learning, namely synchronous and asynchronous strategies. Synchronous itself is a virtual face-to-face between teachers and students at the same time but in different places using video conferencing, google meet and so on, while asynchronous is that the educational process or deepening of material can be done at any time without being limited by time so that it can use technology. communication that is developing a lot today, for example with e learning, Google classrooms, moodle and so on. so that the combination of synchronous and asynchronous strategies in online learning is expected to produce better learning products as one of the principles of online learning itself is independence, Where online learning does not mean not accompanying the learning process but instead must always direct students whenever and wherever.